Patient Experiences With Integrated Pain Care: A Qualitative Evaluation of One VA's Biopsychosocial Approach to Chronic Pain Treatment and Opioid Safety. (April 2019) - Purcell, Natalie; Zamora, Kara; Gibson, Carolyn; Tighe, Jennifer; Chang, Jamie; Grasso, Joseph; Seal, Karen H
Background: Mounting concern about the risks and limited effectiveness of opioid therapy for chronic pain has spurred the implementation of novel integrated biopsychosocial pain care models in health-care systems like the Department of Veterans Affairs (VA). However, little is known about patient experiences with these new care models. Objective: We conducted a qualitative study to examine patient experiences with a pain care model currently being disseminated at the VA: interdisciplinary, integrated pain teams (IPTs) embedded in primary care. Method: We interviewed 41 veterans who received care from VA's first IPT to learn how working with the team impacted their pain care and quality of life. We asked about their overall experience with IPT, what worked and did not work for them, and what changes they would recommend to improve IPT care. Results: The interviews revealed a wide spectrum of patient experiences and varying perspectives on the extent to which the new model improved their pain and quality of life. Thematic analysis shed light on factors impacting patients' experiences, including pretreatment goals and expectations as well as attitudes toward opioids and nonpharmacological treatments. Conclusion: We discuss the implications of our findings for national efforts to implement biopsychosocial pain care, and we offer recommendations to promote patient-centered implementation.